2008
DOI: 10.1177/0095798408316368
|View full text |Cite
|
Sign up to set email alerts
|

Racial Socialization's Moderating Effect Between Poverty Stress and Psychological Symptoms for African American Youth

Abstract: Research indicates that African Americans living in an oppressive society may be at an increased risk of experiencing psychological symptoms. Oppressive society has been defined as the continual denial of resources to marginalized groups. This study examined the possible moderating effects of racial socialization (using Scale of Racial Socialization-Adolescent) in the relationship between poverty and psychological symptoms (externalizing and internalizing symptoms). The sample consisted of 105 African American… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…As indicated in Table , seven studies recruited participants from rural areas, 30 studies recruited participants from urban areas, 18 studies recruited participants from both urban and rural areas, and in four studies recruitment location was unclear. Twelve studies focused exclusively on African American families (Budescu & Taylor, ; Grant et al., ; Grant et al., ; Gutman, McLoyd & Tokoyawa, ; Hurd, Stoddard & Zimmerman, ; Landers‐Potts et al., ; Li, Nussbaum & Richards, ; McLoyd, Jayaratne, Ceballo & Borquez, ; Seaton & Taylor, ; Taylor, Budescu, Gebre & Hodzic, ; Taylor, Rodriguez, Seaton & Dominguez, ; Wilson, Foster, Anderson & Mance, ), five studies focused exclusively on Hispanic and Latino Americans (Loukas & Prelow, ; Loukas, Prelow, Suizzo & Allua, ; Loukas, Suizzo & Prelow, ; Prelow, Loukas & Jordan‐Green, ; White, Liu, Nair & Tein, ), two studies focused exclusively on Asian Americans (Kiang, Andrews, Stein, Supple & Gonzalez, ; Mistry, Benner, Tan & Kim, ), four studies focused exclusively on Whites in America (Conger, Conger, Matthews & Elder, ; Conger et al., ; Gault‐Sherman, ; Simons, Johnson, Beaman, Conger & Whitbeck, ), and one focused on a mixture of racial or ethnic minorities (Tama Leventhal & Brooks‐Gunn, ). Three studies were limited to single parent families (Lehman & Koerner, ; McLoyd et al., ; Simons et al., ), three studies were limited to families with two caregivers (Conger et al., ; Landers‐Potts et al., ), and one study was limited to students with disabilities (Wagner, Newman & Javitz, ).…”
Section: Resultsmentioning
confidence: 99%
“…As indicated in Table , seven studies recruited participants from rural areas, 30 studies recruited participants from urban areas, 18 studies recruited participants from both urban and rural areas, and in four studies recruitment location was unclear. Twelve studies focused exclusively on African American families (Budescu & Taylor, ; Grant et al., ; Grant et al., ; Gutman, McLoyd & Tokoyawa, ; Hurd, Stoddard & Zimmerman, ; Landers‐Potts et al., ; Li, Nussbaum & Richards, ; McLoyd, Jayaratne, Ceballo & Borquez, ; Seaton & Taylor, ; Taylor, Budescu, Gebre & Hodzic, ; Taylor, Rodriguez, Seaton & Dominguez, ; Wilson, Foster, Anderson & Mance, ), five studies focused exclusively on Hispanic and Latino Americans (Loukas & Prelow, ; Loukas, Prelow, Suizzo & Allua, ; Loukas, Suizzo & Prelow, ; Prelow, Loukas & Jordan‐Green, ; White, Liu, Nair & Tein, ), two studies focused exclusively on Asian Americans (Kiang, Andrews, Stein, Supple & Gonzalez, ; Mistry, Benner, Tan & Kim, ), four studies focused exclusively on Whites in America (Conger, Conger, Matthews & Elder, ; Conger et al., ; Gault‐Sherman, ; Simons, Johnson, Beaman, Conger & Whitbeck, ), and one focused on a mixture of racial or ethnic minorities (Tama Leventhal & Brooks‐Gunn, ). Three studies were limited to single parent families (Lehman & Koerner, ; McLoyd et al., ; Simons et al., ), three studies were limited to families with two caregivers (Conger et al., ; Landers‐Potts et al., ), and one study was limited to students with disabilities (Wagner, Newman & Javitz, ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Caughy et al () found that racial pride messages reported by caregivers were associated with fewer reported externalizing behavior problems for boys, but preparation for bias messages were not related to behavioral outcomes. Conversely, Wilson, Foster, Anderson, and Mance () found that adolescents living in poverty who reported high racial socialization messages also reported high externalizing problems. These mixed findings can potentially be explained by differences in gender, SES, and geographic location across the three samples (see Table ).…”
Section: Findings Of the Systematic Research Synthesismentioning
confidence: 99%
“…In an effort to explore the impact of ethnic identification on parenting style, various other statistical tests should be employed. Ethnic identification and racial socialization have been used in several prior studies as a moderator of the relationship between parenting and child outcomes (Wilson et al, 2009;Rodriguez et al, 2008). Future research could test whether the association between overreactive parenting styles and child outcome varies with parental ethnic identification.…”
Section: Resultsmentioning
confidence: 99%
“…Although racial socialization has been used as a moderator of child outcome and parental characteristics, e.g. poverty (Wilson, Foster, Anderson, & Mance, 2009) and mental health and discipline (Rodriguez, McKay, & Bannon, Jr., 2008), less is known of the capacity of ethnic identification to impact characteristics of the parent.…”
Section: Study 3 Black Parenting Power: An Exploratory Analysis Of Thmentioning
confidence: 99%